Basic requirements of laboratory operation for halal analysis - Yuswan, Mohd Hafis; Abdullah Sani, Muhamad Shirwan; Abdul Manaf, Yanty Noorzianna; Mohd Desa, Mohd Nasir (KNE Publishing, 2020)
Analysis of halal food requires that the laboratories conductive the tests adhere to international guidelines and standards. Common worldwide guidelines and standards for laboratory include the ‘International Organization for Standardization 17025’ (ISO 17025), the ‘Good Manufacturing Practice’ (GMP), and ‘Good Laboratory Practice’ (GLP). In halal analysis, the laboratory shall comply with ISO 17025, GMP, and ‘Good Hygiene Practice’ (GHP) as stated in the ‘Manual Procedure for Malaysia Halal Certification’ (MPPHM). This article discusses the basic requirements for laboratory practises, specifically for halal analysis. The study compares these international guidelines with ‘Malaysia Halal Standards’ to demonstrate that these international standards are combined with Islamic practices to produce valid test results using globally recognized best-practices. This promotes confidence in the halal laboratory’s work both nationally and internationally, and will thus improve international trade.